PEMBERDAYAAN WIRAUSAHA DALAM PENDEKATAN ADMINISTRASI PADA NEGOSIASI BISNIS DI RPTRA RAWABADAK SELATAN JAKARTA UTARA - Rafi, Muhammad; Hidajat, Koerniawan (LPPM Universitas Bina Bangsa, 2024)
Business negotiations are one way to develop a business. The current problem is that many people dare to start a business but it doesn't develop until someone goes bankrupt or goes bankrupt. By discussing business negotiations, it is one way to reduce current problems with the material presented, hopefully it will become a reference and knowledge for the community about how to develop a business. delivery of material, discussions and questions and answers related to business negotiations. The socialization method used during community service activities is a participatory approach that invites all participants to be active in the process of delivering material, and forces participants to discuss and ask questions about the discussion. The results obtained during community service activities are that the community knows in detail about business negotiations, prepares steps before carrying out negotiations, and discusses various ways to reach agreements with consumers. Not only is knowledge gained, but as a means of meeting and discussing with the community, this service is very meaningful and beneficial for the community and students